Mystery of Divine Stories - Hayitov, Shavkat (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract: The article describes Alisher Navoi’s attitude to theology, the ability to use Quranic stories and symbols in the interpretation of artistic ideas. It is proven that the moral-educational, spiritual-enlightenment views of the great thinker, who relied on the truth of the divine stories, found deep expression in the artistic text. The qualities of perfection expressed in "Mahbub ul- Qulub" by Hazrat Alisher Navoi, issues of Islamic and human faith are analyzed, and the main attention is focused on the importance of this in raising the sense of perfection in the children of the Independence period.